Object Counter / Norhazima Abd. Kadir and Noor Hazalina Che Ahmad - Abd. Kadir, Norhazima; Che Ahmad, Noor Hazalina (2002)
An Object Counter is present a combination between CMOS, decoder and counter integrated circuit (lCs) presented by CD4093 quad 2-input NAND Schmitt trigger, CD4511 BCD to seven segment latch decoder-driver and CD4518 dual BCD up counter. The circuit is use for counting any object and any object and can count between 1 to 9999. For the same additional circuit, we can have audio or visual indicator after a specified number of counting that we can set between the range. In this prototype, the distance between light source and the phototransistor was about 10cm only The circuit has an advantages of using very low power consumption, wide supply voltage range, good noise immunity and has high package density The project can be an accessory at any place because the circuit small value of current and light weight.